PENGARUH FRAUD TRIANGLE DAN EQUITY SENSITIVITY TERHADAP PERILAKU ETIS STUDY FROM HOME - Renata Dea Puspita (TEMA, 2021)
This research has a purpose to find out and analyze the ethical behavior of accounting students during the COVID-19 pandemic which is reviewed from fraud triangle and equity sensitivity. Learning is done by online methods or commonly known as study from home. The object of this study is an Accounting student of the Faculty of Economics and Business Brawijaya University class of 2016, 2017, and 2018. Based on the purposive sampling method and calculation using the slovin formula obtained a sample of 83 respondents who can be used as a sample and in accordance with the conditions in filling out the questionnaire. Data sources are used using primary and secondary data sources. The primary data source is obtained directly from the results of filling out questionnaires that have been disseminated by researchers. While secondary data obtained from related agencies in this study is academic FEB UB. Analysis of data in this study using SPSS software with the results showed that fraud triangle affects the ethical behavior of accounting students when study from home and equity sensitivity has no effect on ethical behavior of accounting students when study from home.   Penelitian ini bertujuan untuk mengetahui dan menganalisis perilaku etis mahasiswa akuntansi selama masa pandemic COVID-19 yang ditinjau dari fraud triangle dan equity sensitivity. Pembelajaran dilakukan dengan metode online atau yang biasa dikenal dengan istilah kuliah daring. Objek penelitian ini adalah mahasiswa akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya angkatan 2016, 2017, dan 2018. Berdasarkan metode purposive sampling dan perhitungan rumus slovin diperoleh sampel sebanyak 83 responden yang dapat dijadikan sampel dan sesuai dengan syarat-syarat dalam pengisian kuesioner. Sumber data yang digunakan menggunakan sumber data primer dan sekunder. Sumber data primer diperoleh langsung dari hasil pengisian kuesioner yang telah disebar oleh peneliti. Sedangkan data sekunder diperoleh dari instansi terkait dalam penelitian ini adalah akademik FEB UB. Analisis data dalam penelitian ini menggunakan software SPSS dengan hasil menunjukkan bahwa fraud triangle berpengaruh terhadap perilaku etis mahasiswa akuntansi saat study from home dan equity sensitivity tidak berpengaruh terhadap perilaku etis mahasiswa akuntansi saat study from home.